Genistein From Fructus sophorae Protects Mice From Radiation-Induced Intestinal Injury - Zhang, Jieyu; Pang, Zhijun; Zhang, Yuting; Liu, Jiaxin; Wang, Zhaowei; Xu, Chuanyang; He, Lei; Li, Weina; Zhang, Kuo; Zhang, Wangqian; Wang, Shuning; Zhang, Cun; et al. (Frontiers in Pharmacology, 2021)
The development of an effective pharmacological countermeasure is needed to reduce the morbidity and mortality in high-dose ionizing radiation-induced acute damage. Genistein has shown bioactivity in alleviating radiation damage and is currently synthesized by chemosynthetic methods. Due to concerns about chemical residues and high costs, the clinical application of genistein is still a major challenge. In this study, we aimed to establish an efficient method for the extraction of genistein from Fructus sophorae. The effects of extracted genistein (FSGen) on preventing intestinal injury from radiation were further investigated in this study. C57/BL mice were exposed to 7.5 Gy whole body irradiation with and without FSGen treatments. Histological analysis demonstrated significant structural and functional restitution of the intestine and bone marrow in FSGen-pretreated cohorts after irradiation. Through mRNA expression, protein expression, and small interfering RNA analyses, we demonstrated that FSGen protects IEC-6 cells against radiation damage by upregulating the Rassf1a and Ercc1 genes to effectively attenuate DNA irradiation damage. Together, our data established an effective method to extract genistein from the fructus sophorae plant with high purity, and validated the beneficial roles of the FSGen in protecting the radiation damage. These results promise the future applications of Fructus sophorae extracted genistein in the protection of radiation related damages.